UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI MELALUI BERMAIN KOLASE DARI BAHAN KAIN PERCA PADA KELOMPOK B RA PERSIS 421 AL-ITTIHAD KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA - Esih Sukaesih; Munawar Hadiatin; Tetin Nurfitri (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
Children's fine motor skills are movements that involve body parts in coordinating dexterity or skills. Involves the smooth muscles of the hands and fingers, requiring hand-eye coordination (eg collage activities). Collage activities are activities that teach children to be more creative, patient and independent. The purpose of this study is to improve children's fine motor skills through playing collage with patchwork in group B RA Persis 421 Al-Ittihad, Cipatujah District, Tasikmalaya Regency, a classroom action research (CAR). This research consisted of two cycles, including planning, implementation, observation, and reflection activities. In each cycle, three meetings were held. The subjects of this study were 9 children, 6 boys and 3 girls. Data collection techniques used observation and documentation techniques. The results showed that there was an increase in the fine motor skills of children in group B RA Persis 421 Al-Ittihad, Cipatujah District, Tasikmalaya Regency through collage play activities with patchwork which can be seen from the increase in children starting from cycle I to cycle II which shows that fine motor skills has reached the expected development criteria, namely BSH (Developing As Expected).